Safety of sublingual immunotherapy Timothy grass tablet in subjects with allergic rhinitis with or without conjunctivitis and history of asthma. Issue 3 (14th January 2015) - Maloney, J.; Durham, S.; Skoner, D.; Dahl, R.; Bufe, A.; Bernstein, D.; Murphy, K.; Waserman, S.; Berman, G.; White, M.; Kaur, A.; Nolte, H.
Abstract Background Patients with asthma may be more susceptible to adverse events (AEs) with sublingual immunotherapy tablet (SLIT‐tablet) treatment, such as severe systemic reactions and asthma‐related events. Using data from eight trials of grass SLIT‐tablet in subjects with allergic rhinitis with/without conjunctivitis (AR/C), AE frequencies were determined in adults and children with and without reported asthma. Methods Data from randomized, double‐blind, placebo‐controlled trials of Timothy grass SLIT‐tablet MK‐7243 (2800 BAU/75 000 SQ‐T, Merck/ALK‐Abelló) were pooled for post hoc analyses. Subjects with uncontrolled and severe asthma were excluded from the trials. Frequencies for treatment‐emergent AEs (TEAEs), local allergic swelling (mouth or throat), systemic allergic reactions, and asthma‐related treatment‐related AEs (TRAEs) were calculated. Results Among adults (n = 3314) and children (n = 881), 24% and 31%, respectively, had reported asthma. No serious local allergic swellings or serious systemic allergic reactions occurred in subjects with asthma treated with SLIT‐tablet. There was no evidence of increased TEAEs, systemic allergic reactions, or severe local allergic swellings in adults or children with asthma treated with grass SLIT‐tablet versus subjects without asthma in or outside of pollen season. There were 6/120 asthma‐related TRAEs assessed as severe with grass SLIT‐tablet and 2/60 with placebo, without a consistent trend among subjects with and without asthma (5 and 3 events, respectively). Conclusions In the AR/C subjects with reported well‐controlled mild asthma included in these studies, grass SLIT‐tablet did not increase TEAE frequency, severe local allergic swelling, or systemic allergic reactions versus subjects without asthma. There was no indication that treatment led to acute asthma worsening.